Предмет: Математика,
автор: vlad1491
(m+1)(m+3)-(1-7m)-(2-m) упростите
Ответы
Автор ответа:
1
Ответ:
m в квадрате + 1 в квадрате - 1+7м -2+м
Пошаговое объяснение:
Автор ответа:
1
(m + 1)(m + 3) - (1 - 7m)(1 + 7m) - (2 - m) = m² + 3m + m + 3 - (1 - 49m²) - 2 + m = m² + 3m + m + 3 - 1 + 49m² - 2 + m = 50m² + 5m + 0 = 50m² + 5m
Похожие вопросы
Предмет: Русский язык,
автор: elenastruchkova
Предмет: Русский язык,
автор: DashaNickolaeva
Предмет: Русский язык,
автор: Tamago22
Предмет: Литература,
автор: sargsyantatev1